2015
DOI: 10.1007/s10195-015-0345-z
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors for early infection in patients with open fractures and proposal for a risk score

Abstract: BackgroundThe primary goals of orthopedic treatment of open fractures are to prevent infection, stabilize bone injury and restore limb function. The objective of the current study was to identify risk factors associated with infection in patients suffering from open fractures, using the strength of association of these factors to propose a score that enables risk stratification in initial care.Materials and methodsA retrospective analysis was performed on 122 patients who underwent open fracture treatment. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Internal fixation was compared to external fixation in 16 studies (four RCTs, five prospective, eight retrospective) [8,21,22,24,35,39,50,54,114,115,118,141,[171][172][173][174][175]. Heterogeneity was large (p=<0.00001, I 2 =79%); sensitivity analysis did not change this.…”
Section: Fixation Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…Internal fixation was compared to external fixation in 16 studies (four RCTs, five prospective, eight retrospective) [8,21,22,24,35,39,50,54,114,115,118,141,[171][172][173][174][175]. Heterogeneity was large (p=<0.00001, I 2 =79%); sensitivity analysis did not change this.…”
Section: Fixation Methodsmentioning
confidence: 98%
“…Thirteen articles mentioned age as a risk factor, most reported mean age (N=10, 1,819 fractures), [8,[17][18][19][20][21][22][23][24][25] others median age (N=3, 1,477 fractures) [26][27][28]. Using those that presented age in means with standard deviations (SD) did not demonstrate significant differences between infected and non-infected patients.…”
Section: Agementioning
confidence: 99%
See 2 more Smart Citations
“…Bowen and Widmaier 6 investigated risk factors for infection after open fractures, and the only predictor for infection they found was tobacco use. Matos et al 16 also looked for risk factors for acute infection in open fractures and found an association between increased time until treatment and risk of infection. Oliveira et al 17 analyzed the risk of infection in 1,103 patients with closed fractures who underwent internal fixation compared with 1,887 open fractures, and found a higher incidence of infection in cases of exposed fractures.…”
Section: Discussionmentioning
confidence: 99%